2017
DOI: 10.1515/cclm-2017-0873
|View full text |Cite
|
Sign up to set email alerts
|

Association of adrenal hormone metabolites and mortality over a 6-year follow-up in COPD patients with acute exacerbation

Abstract: Independent of age, gender, corticosteroid exposure and exacerbation type, adrenal hormones are associated with mortality at short and long term in patients with COPD exacerbation with different time-dependent effects of glucocorticoids, androgens and mineralocorticoids. A better physiopathological understanding of the causality of these effects may have therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…DHEA has benefited patients with COPD [28,33] and pulmonary hypertension [28,34] in small trials, as well as animal models [35,36]. Therefore, we hypothesize that DHEA treatment may also improve asthma outcomes.…”
Section: Background and Significance Regarding Androgens For Patientsmentioning
confidence: 95%
“…DHEA has benefited patients with COPD [28,33] and pulmonary hypertension [28,34] in small trials, as well as animal models [35,36]. Therefore, we hypothesize that DHEA treatment may also improve asthma outcomes.…”
Section: Background and Significance Regarding Androgens For Patientsmentioning
confidence: 95%
“…DHEA and DHEA-S are also lower in patients with COPD than in healthy controls, and COPD leads to pulmonary hypertension (PH). DHEA supplementation improved the 6-min walk test, pulmonary hemodynamics, and the diffusing capacity of the lungs for carbon monoxide of patients with PH-COPD (311,312). The therapeutic potential of DHEA is currently being investigated in 24 patients with PH in the EDIPHY (Effects of DHEA in Pulmonary Hypertension) trial.…”
Section: Testosterone and Dhea Administration In Asthma And Copdmentioning
confidence: 99%
“…Metabolites of glycolysis are fed into PPP to generate nicotinamide adenine dinucleotide phosphate, which is employed for fatty acid biosynthesis and antioxidant protection [89]. Metabolomic analysis found that PPP was activated in COPD patients with CS exposure [90], which might be a protective mechanism to alleviate oxidative stress. In addition, the abnormal citrate level in COPD reflects the disturbance of TCA cycle, which might be associated with the decreased activities of enzymes involved in oxidative energy metabolism and mitochondrial dysfunction [91].…”
Section: The Role Of Metabolism Dysfunction In Copd Pathogenesismentioning
confidence: 99%